Human-Computer Interaction Based On The Function Of ‎Management Information Systems In Business - Rawat, Manoj Kumar; Gulati, Sagar; Kumar , Sumit; Selvakumar, Dr.S.; Kusumanchi, T.P.S. Kumar (International Journal of Basic and Applied Sciences, 2025)
The discipline of management information systems (MIS) is new and distinct, undergoing ongoing upheaval and rapid evolution. As a ‎result, MIS research must contend with two shifts: relevance and rigor. Numerous research approaches offer different combinations of ‎relevance and rigor. The economic analysis of information as a commodity in business management is the basis for the linkages that ‎determine the value of the information research stream. The focus of the human-computer systems design research stream is on the cognitive ‎underpinnings of successful systems configuration. The locus of the value of the IS investment is the emphasis of the IS organization and ‎strategy research stream, rather than the opinions of a system or its user. Since management information systems are used to examine ‎organizational operations, they differ from other information systems. In academia, the phrase is frequently used to describe data ‎management techniques related to the automation or assistance of human decision-making, such as executive information systems, talented ‎systems, and decision-making systems. Organizations require different MIS types to support a range of organizational levels, roles, and ‎company processes. In this article, an attempt has been made to examine the function of MIS as a business opportunity and a challenge‎.